Disclosure when the Market is Unsure of Information Endowment of Managers - KWON, Young Koan (Institutional Knowledge at Singapore Management University, 1988)
The article focuses on information disclosure by management in uncertain markets. It mentions that when management doesn't disclose information, investors are left to wonder if the lack of information disclosure is due to the lack of knowledge by managers or due to the adverse content of the information. It suggests that this uncertainty by investors results to partial disclosure in equilibrium. It presents mathematical models for the potential events of management not having information, management withholding information, and management disclosing information. It suggests that management can be determined to have withheld information if in the wake of investors independently learning of bad news, managers disclose information revealing the news isn't as bad as feared.